A comprehensive analysis of serum D-dimer and Ferritin levels, in 347 patients with severe (breathlessness and chest discomfort) corona virus disease 2019 - Jangamgudem, Sudharani (International Journal of Research in Medical Sciences, 2022)
Background: This study aimed to evaluate the association between serum D-dimer and Ferritin levels, in patients with severe (Breathlessness and chest discomfort) corona virus disease 2019. Methods: The present study included a 347 (out of 1500) patients with severe Breathlessness and Chest discomfort age between 40 to 60 years who were confirmed to have Covid-19 based on RTPCR in a GVPIHC&MT referral hospital between 2020 June and 2020 August, were analysed. Results: A total No of 694 cases were studied by dividing them into two groups controls 347 and cases 347. The results so obtained compare with 347 healthy controls included in this study. Statistical evaluation was carried out to confirm any deviation from the normal values. The Mean± SD Serum FERRITIN Cases (654.45±317.45), controls (157.03±87.43), D-dimer values of cases (6.1517±3.4270), controls (0.2204±0.1083) and both serum Ferritin and D-dimer values in cases (3.443230±3.625471), controls (0.201372±0.121560). This increase is statistically P value highly significant (<0.001) Conclusions: It has been shown from this study with, the serum activities of D-Dimer and Ferritin levels were markedly increased in Severe Breathlessness and Chest discomfort in male and female COVID-19 patients.